Potensi Guru-guru Kabupaten Lombok Barat dalam Mengembangkan Profesinya melalui Penyusunan Karya Ilmiah - Rokhmat, Joni -; Herianto, Edy -; Wildan, Wildan - (Universitas Mataram, 2023)
This community service aims to explore the potential of teachers in developing their profession through the preparation of scientific work and providing direction in compiling scientific work. This service was carried out using lecture, question, and answer methods as well as work training (workshops), involved 30 senior high school teachers in West Lombok Regency. The results of the discussion showed that the teachers were very enthusiastic about participating in the activity but even though this activity was not new the majority still did not understand how to prepare proposals, instruments, to carry out classroom action research as well as how to write scientific articles, especially research articles. Meanwhile, the results of the questionnaire analysis showed that all participants of this service activity did not yet have scientific publications even though some of them already needed them. So basically these teachers have the potential to develop their profession through the preparation of scientific work. As an obstacle is not yet know how to write scientific work, and there is no time because the workload is quite massive. About this activity, they suggest that this activity is carried out routinely, once or twice a year at the school level to the Subject Teachers Association, including the need to establish cooperation with tertiary institutions